No System Is Perfect: Understanding How Registration‐Based Editorial Processes Affect Reproducibility and Investment in Research Quality - BLOOMFIELD, ROBERT; RENNEKAMP, KRISTINA; STEENHOVEN, BLAKE (Journal of Accounting Research, 2018)
ABSTRACT The papers in this volume were published through a Registration‐based Editorial Process (REP). Authors submitted proposals to gather and analyze data; successful proposals were guaranteed publication as long as the authors lived up to their commitments, regardless of whether results supported their predictions. To understand how REP differs from the Traditional Editorial Process (TEP), we analyze the papers themselves; conference comments; a survey of conference authors, reviewers, and attendees; and a survey of authors who have successfully published under TEP. We find that REP increases up‐front investment in planning, data gathering, and analysis, but reduces follow‐up investment after results are known. This shift in investment makes individual results more reproducible, but leaves articles less thorough and refined. REP could be improved by encouraging selected forms of follow‐up investment that survey respondents believe are usually used under TEP to make papers more informative, focused, and accurate at little risk of overstatement.